2010
DOI: 10.1007/s11145-009-9223-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-service teachers’ receptive vocabulary knowledge on their interactive read-alouds with elementary school students

Abstract: There are individual differences in the amount and type of vocabulary that adults produce to young children in the home environment before the children enter school. How many words a mother knows is a significant predictor of a child's vocabulary. The current study addressed the question of whether there were individual differences in the amount and type of vocabulary that pre-service teachers produced in their first read-aloud lessons to first and second grade students. Specifically, would pre-service teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
1
2
0
1
Order By: Relevance
“…Instead, our findings suggest that teachers’ use of complex language may be something more intrinsic—more of a personal style of speaking. This conjecture is consistent with the findings of a recent study showing that elementary school teachers’ own vocabulary knowledge was related to their classroom language use (Corrigan, 2010). Specifically, Corrigan (2010) found that teachers who evidenced higher vocabulary performance on a receptive vocabulary measure tended to use more sophisticated and diverse language to address their first‐ and second‐grade students than teachers with lower vocabulary skills.…”
Section: Discussionsupporting
confidence: 92%
“…Instead, our findings suggest that teachers’ use of complex language may be something more intrinsic—more of a personal style of speaking. This conjecture is consistent with the findings of a recent study showing that elementary school teachers’ own vocabulary knowledge was related to their classroom language use (Corrigan, 2010). Specifically, Corrigan (2010) found that teachers who evidenced higher vocabulary performance on a receptive vocabulary measure tended to use more sophisticated and diverse language to address their first‐ and second‐grade students than teachers with lower vocabulary skills.…”
Section: Discussionsupporting
confidence: 92%
“…In light of these findings of the stability of individual teacher's language use, together with those of recent studies showing that teachers' language use varies as a function of their own knowledge of language (Corrigan, 2011), it is important to consider, empirically, the ways in which the teacher's language use may be amenable to change. Indeed, there may be several possible strategies and tools to investigate as platforms for doing so; these include working with teachers on rephrasing and recasting features of their own language, and/or designing and implementing classroom-based reading comprehension programs and interventions aimed at increasing sophisticated language use in the classroom, by students and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, teachers play a critical role in creating an environment that fosters multiple learning opportunities during interactive read‐aloud sessions (Sipe, 2008), through encouraging active student participation and creating an environment that provides children with opportunities to express themselves and share their experiences (Lennox, 2013; Wiseman, 2011). However, while research on interactive read‐alouds has primarily focused on experienced teachers, few studies have explored preservice teachers and their use of interactive read‐alouds to discuss social issues such as equity and injustice (Corrigan, 2011; Pendergast et al., 2015). Hence, there is a need for further research to explore how preservice teachers use interactive read‐alouds to promote critical thinking and discussion of social issues, such as women's inequality, in early childhood education.…”
Section: Representation Of Women In Children's Literature and Interac...mentioning
confidence: 99%